Pendampingan Literasi Penggunaan Mobile Banking Syariah Pada Masyarakat Desa Air Buluh Kecamatan Ipuh Kabupaten Mukomuko - Dhef Vindra; Desi Isnaini; Khairiah Elwardah (KENDURI : Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2024)
The activities carried out were the Opening of the Activity, Socialization of Mobile Banking introduction with BSI, Installation and Teaching the use of the Mobile Banking application, Interviews with the community who participated in the mentoring to find out the results of the mentoring, Closing the activity. The mentoring activities in the Air Buluh Village community, Ipuh District, can increase the understanding of the Air Buluh Village community by 15 out of 20 people regarding the Mobile Banking application and how to use it. The problem faced by the researcher was the inappropriate time of the mentoring because the average work of the Air Buluh Village community is oil palm farmers, both privately owned and PT, which resulted in the community having to take care of their work first, in overcoming this, the activity was carried out from house to house and made an appointment in advance to determine free time for the community. The party involved was one of the BSI KCP Mukomuko employees named Meydina Putri. This mentoring was carried out from September to December, the costs incurred in this mentoring activity were Rp. 565,000